Spatiotemporal Pattern of a Macrofungal Genus Phylloporia (Basidiomycota) Revealing Its Adaptive Evolution in China - Xue-Wei Wang; Li-Wei Zhou (Journal of Fungi)
The understanding of distribution and the evolutionary scenario is crucial for the utilization and conservation of biological resources; nevertheless, such explorations rarely focus on macrofungi. The current study selects a macrofungal genus, Phylloporia, and explores its spatiotemporal pattern in China. A total of 117 available occurrence records of Phylloporia in China were summarized for the current analyses. Ensemble modeling supports the highly suitable habitat of Phylloporia concentrated in southern, especially southeastern, China, where the ancestor of Phylloporia originated 77.74 million years ago and then dispersed to other parts of China. Benefitting from the available suitable habitats, Phylloporia rapidly diversified after its divergence in Southeast China. Then, the net diversification rate slowed down when the rapidly diversifying species filled available niches in Southeast China and the dispersed species in other parts of China inhabited the less suitable and unsuitable habitats. During adaptive evolution, precipitation, temperature and the host plant are the major environmental variables that shape the spatiotemporal pattern of Phylloporia. In conclusion, the current study reveals the adaptive evolutionary scenario of Phylloporia and provides the first exploration of the spatiotemporal pattern of macrofungi.